"Thou Trade which didst sustaine my poverty": Thomas Heywood's The Four Prentices of London and the Emergence of a Rhetorical Counterpublic. Issue 2 (November 2017) - Heverin, Drew
Abstract : This essay investigates how the depiction of apprenticeship in Thomas Heywood's early play The Four Prentices of London participated in the formation of a marginalized rhetorical community on the Elizabethan stage. Contributing to a larger early modern counterpublic, this play publicized the private discussion of the outspoken if disenfranchised apprentices of Renaissance London by placing the marginalized concerns of these young men in direct conversation with the public's aspirational understanding of the guilds' training system. In his young and dynamic protagonist Eustace, Heywood stages a direct challenge to the narrow understanding of a riotous apprentice and offers a nuanced take on the institution itself – one that honors the possibility of social mobility but recognizes the cost of pursuing it. In The Four Prentices, Heywood uses the rhetoric of this marginalized urban cohort to theatrically refashion the Elizabethan public sphere and makes room for the apprentices in the public deliberations of the early modern city. In this essay, I argue that Heywood brings attention to the concerns of London's apprentices and, thus, recognizes the authority of this counterpublic within the larger urban public sphere.